2005
DOI: 10.1097/01.smj.0000136261.21711.85
|View full text |Cite
|
Sign up to set email alerts
|

Impact of National Low Back Pain Guidelines on Clinical Practice

Abstract: The AHRQ clinical practice guidelines for the management of acute low back pain had a modest impact on physician behavior, increasing the use of acetaminophen and nonsteroidals and decreasing the use of muscle relaxants and physical therapy referrals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…We found that 30% of subjects received PT at some point in the year after a physician visit for a new episode of back pain. This is more than Gellhorn et al [11] reported in a large cohort of Medicare beneficiaries, 16% within 1 year, but it is similar to studies using data from the National Ambulatory Medical Care Survey, where PT referrals were made in 21% to 27% of cases [34,35].…”
Section: Discussionsupporting
confidence: 76%
“…We found that 30% of subjects received PT at some point in the year after a physician visit for a new episode of back pain. This is more than Gellhorn et al [11] reported in a large cohort of Medicare beneficiaries, 16% within 1 year, but it is similar to studies using data from the National Ambulatory Medical Care Survey, where PT referrals were made in 21% to 27% of cases [34,35].…”
Section: Discussionsupporting
confidence: 76%
“…7–9 Prior research among patients with back pain revealed significant increases in use of CT/MRI exams, outpatient surgical procedures, and narcotic prescriptions, but many of these studies are over a decade old, limited to specific populations (e.g., Medicare), or study different aspects of utilization such as surgeries or hospitalizations. 6,1015 …”
mentioning
confidence: 99%
“…Whether CPGs are worth the resources that continue to be dedicated to them remains a matter of speculation. 40 …”
Section: Review Of Clinical Practice Guidelines For Low Back Painmentioning
confidence: 99%